In vivo biocontrol potential of Bacillus plant growth-promoting rhizobacteria against pectinolytic plant pathogens - Benaissa, Asmaa; Bestami, Merdia; Fellan, Kheira; Benmalek, Rokaia (Folia microbiologica, 2025)
Bacillus is well known for producing a wide range of compounds that inhibit microbial phytopathogens. From this perspective, we were interested in evaluating the biocontrol potential of 5 plant growth-promoting rhizobacteria Bacillus species (PGPR-Bacillus) on 21 microbial pectinolytic plant pathogens isolated from previous studies. Phytopathogenicity and in vivo biocontrol potential of PGPR curative and preventive treatments were investigated from this angle. Overall, the pathogenicity test on healthy tomato, zucchini, and mandarin showed low rot to no symptoms for all PGPR strain culture treatments. Conversely, zucchini pre-treated with PGPR strains B. circulans and B. cereus for 72 h showed no signs of soft rot and remained healthy when in vitro contaminated with phytopathogens (Neisseria cinerea and Pichia anomala). Additionally, the PGPR-Bacillus strains were shown to be effective in mitigating the symptoms of soft rot in tomatoes, zucchini, and oranges using in vivo curative treatment. It is true that the majority of pectinolytic phytopathogenic strains exhibited antibiotic resistance. In vivo tests revealed that PGPR-Bacillus cell culture was effective against plant pathogens. Thus, PGPR-Bacillus can be considered a potential biocontrol agent for pectinolytic plant pathogens.
Keywords: Pest Control, Biological; biologická ochrana; vývoj rostlin; Citrus; Biological Control Agents; půdní mikrobiologie; antibióza; PGPR; Antibiosis; Plant Development; Bacillus; Pectins; nemoci rostlin; biologická kontrola škůdců; Plant Diseases; Solanum lycopersicum; Biocontrol; Phytopathogenic pectinolytic; pektiny; Soil Microbiology